Pronounced antiseizure activity of the subtype‐selective GABAA positive allosteric modulator darigabat in a mouse model of drug‐resistant focal epilepsy. (14th August 2022) - Gurrell, Rachel; Iredale, Philip; Evrard, Alexis; Duveau, Venceslas; Ruggiero, Céline; Roucard, Corinne
Abstract: Aim: Darigabat is an α2/3/5 subunit‐selective positive allosteric modulator of GABAA receptors that has demonstrated broad‐spectrum activity in several preclinical models of epilepsy as well as in a clinical photoepilepsy trial. The objective here was to assess the acute antiseizure effect of darigabat in the mesial temporal lobe epilepsy (MTLE) mouse model of drug‐resistant focal seizures. Methods: The MTLE model is generated by single unilateral intrahippocampal injection of low dose (1 nmole) kainic acid in adult mice, and subsequent epileptiform activity is recorded following implantation of a bipolar electrode under general anesthesia. After a period of epileptogenesis ( 4 weeks), spontaneous and recurrent hippocampal paroxysmal discharges (HPD; focal seizures) are recorded using intracerebral electroencephalography. The number and cumulated duration of HPDs were recorded following administration of vehicle (PO), darigabat (0.3–10 mg kg −1, PO), and positive control diazepam (2 mg kg −1, IP). RESULTS: Darigabat dose‐dependently reduced the expression of HPDs, demonstrating comparable efficacy profile to diazepam at doses of 3 and 10 mg kg −1 . CONCLUSIONS: Darigabat exhibited a robust efficacy profile in the MTLE model, a preclinical model of drug‐resistant focal epilepsy. A Phase II proof‐of‐concept placebo‐controlled, adjunctive‐therapy trial (NCT04244175) is ongoing to evaluate efficacy and safety of darigabat in patients with drug‐resistant focal seizures. Abstract : The antiseizure effect of darigabat, an α2/3/5 subunit‐selective GABAA receptor positive allosteric modulator, was examined in the mesial temporal lobe epilepsy mouse model of drug‐resistant focal seizures. Darigabat exhibited a robust dose‐dependent reduction in focal seizures (hippocampal paroxysmal discharges) in the model, indicating that selective modulation of GABAA receptors may have a clinical utility in patients with drug‐resistant focal seizures.